Thémata. Revista de Filosofía: Nueva Era - Choza, Jacinto (THÉMATA. Revista de Filosofía, 2013)
Thémata. Revista de Filosofía: Nueva Era<a class="ext" style="box-sizing: border-box; color: #336699; text-decoration: none; font-size: 11px; font-family: Arial, Helvetica, sans-serif; margin: 0px; padding: 0px; border: 0px; line-height: 15.3999996185303px; text-align: justify; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;" href="http://institucional.us.es/revistas/themata/47/art_1.pdf" target="_blank">Thémata. Revista de Filosofía: Nueva Era